Pengaruh Harga Minyak Dunia, Index Dow Jones, Suku Bunga Bank Indonesia dan Inflasi Terhadap IHSG Tahun 2020 - 2023 - Istianah; Meliza (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Macroeconomic conditions greatly influence the JCI movement. When events or changes in global economic conditions occur, such as a financial crisis in developed countries or political turmoil in certain regions, this can affect investor sentiment globally. This study aims to determine and analyze the influence of world oil prices, the Dow Jones index, the Indonesian Bank interest rate, and inflation on the Indonesian Stock Exchange (IHSG). The population in this study consists of IHSG data from 2020 to 2023. The sampling technique used in this study is a census technique where the entire population of the study is taken as a sample. The analytical tool used is multiple linear regression. The results of this study indicate that world oil prices, the Dow Jones index, the Indonesian Bank interest rate, and inflation have an influence on the IHSG. For investors is to pay attention to macroeconomic conditions, both national and global, before investing to minimize risks and for future researchers to continue research by adding other macroeconomic variables.